1993
DOI: 10.1677/joe.0.1370043
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile prolactin secretory patterns throughout the oestrous cycle in the rat

Abstract: Prolactin secretion throughout the oestrous cycle in the rat remains at a low level and fairly constant, with the exception of the surge at pro-oestrus. The present study was designed to characterize possible changes in pulsatile patterns of prolactin during the oestrous cycle of the adult female rat. Mean values of prolactin increased from dioestrus-2 to pro-oestrus and then decreased to the values found at dioestrus-1. The number of peaks remained fairly constant in any phase of the oestrous cycle. The absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…In humans and rats, pituitary prolactin release is both pulsatile and nyctohemeral [1][2][3][4]. Also, in female dogs, a pulsatile secretion pattern for prolactin has been demonstrated [5], while in male dogs a pulsatile secretion of this hormone is only suggested considering spontaneously elevated prolactin concentrations found in individual but not all dogs [6].…”
Section: Introductionmentioning
confidence: 99%
“…In humans and rats, pituitary prolactin release is both pulsatile and nyctohemeral [1][2][3][4]. Also, in female dogs, a pulsatile secretion pattern for prolactin has been demonstrated [5], while in male dogs a pulsatile secretion of this hormone is only suggested considering spontaneously elevated prolactin concentrations found in individual but not all dogs [6].…”
Section: Introductionmentioning
confidence: 99%
“…All those studies were performed in the so called basal conditions, although prolactin, like other pituitary hormones, is secreted following a ultradian episodic pattern (Lafuente et al, 1993(Lafuente et al, , 1994. Thus an effect of NO on this mechanism could be foreseen.…”
Section: Introductionmentioning
confidence: 99%
“…I m l/100 g body weight) and atrial cannulas were implanted through the external jugular vein according to procedures used in previous studies [11,14], This procedure allows the animals to move freely in their cages during the period of bleeding.…”
Section: Cannula Implantationmentioning
confidence: 99%
“…Hyperprolactinemia was associated with diminished, unchanged or increased plasma LH levels [9]. Prolactin and/or LH are released in an episodic fash ion [10][11][12][13] that can be modified by hyperprolactinemia [14] through mechanisms which are not fully under stood. Previous studies showed that prolactin interferes with the pulsatile release of LHRH [15], thus modifying gonadal function.…”
Section: Introductionmentioning
confidence: 99%